Teaching communication skills: Using Gagne's model as an illustration - Lo, Wen-Lin (Tzu Chi Med J, 2019)
Communication skills is an essential competence for physicians. Good communication skills correlate with higher patient satisfaction and overall patient outcome. Therefore, such training should start as early as in the undergraduate curriculum with experiential methods and more advanced skills to be integrated at different levels. Design of the training program should prepare for the transfer of communication skills into the clinical setting. Supervision from clinician educators could enhance the transfer of communication skills. Faculty development programs could help clinician educators to develop teaching skills needed in teaching communication. Continuous feedback from teachers and reflective practice of the learners are essential for effective learning of communication skills. The design of the teaching should be based on theory such as adult learning theory or experiential learning. Gagne's model provides a template for the systemic design of instructional events, and this article will illustrate an example of teaching communication skills based on the model.